2021
DOI: 10.22159/ijap.2021v13i1.39608
|View full text |Cite
|
Sign up to set email alerts
|

Rp-HPLC (Stability-Indicating) Based Assay Method for the Simultaneous Estimation of Doravirine, Tenofovir Disoproxil Fumarate and Lamivudine

Abstract: Objective: In this study, a RP-HPLC (stability-indicating) based assay method for the estimation of doravirine (DRV), tenofovir disoproxil fumarate (TFF) and lamivudine (LMV) simultaneously in the tablets was described. Methods: The simultaneous analysis of DRV, TFF and LMV was done with HPLC system (Agilent 1100 series) and Luna Phenomenex C18 (250 mm × 4.6 mm × 5 μ) column with isocratic mobile phase (35% volume ratio of methanol and 65% volume ratio of 20 mmol ammonium formate, pH 5). Validation of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Only a validated method should be employed for the estimation of drugs. The developed method was validated following the ICH Q2 (R1) guidelines and other literatures using the prescribed validation parameters [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Methods Validationmentioning
confidence: 99%
“…Only a validated method should be employed for the estimation of drugs. The developed method was validated following the ICH Q2 (R1) guidelines and other literatures using the prescribed validation parameters [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Methods Validationmentioning
confidence: 99%
“…The literature search reveals that various analytical techniques have been employed for the quantification of DOR (Doravirine), TDF (Tenofovir disoproxil fumarate), and LMV (Lamivudine), both in combination and individually. Some of the widely used methods include high-performance liquid chromatography (HPLC) and ultraperformance liquid chromatography (UPLC), which have been referenced in several studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Additionally, a high-pressure thin-layer chromatography (HPTLC) method has been reported for the quantification of LMV and TDF alone and in combination [17][18][19][20][21][22][23][24][25][26].…”
Section: Robustnessmentioning
confidence: 99%
“…Previous literature searches revealed that various other analytical techniques, such as high-performance liquid chromatography (HPLC) [2][3][4][5][6][7][8][9][10][11][12][13], ultra-performance liquid chromatography (UPLC) [14][15][16], have been employed for the quantification of DOR, TDF, and LMV in combination and alone. High-pressure thin layer chromatography (HPTLC) [17][18][19][20][21][22][23][24][25][26] method has been reported for quantification alone and in combination with LMV and TDF.…”
Section: Introductionmentioning
confidence: 99%
“…It was approved by the US Food and Medication Administration in 2018 as a complete drug regimen for HIV type 1 infection in patients who had not previously received antiretroviral therapy [12]. According to the literature, few techniques have been published for estimating Lamivudine, Tenofovir, and Doravirine alone and in combination with various dosage forms utilising UV, HPLC methods [13][14][15]. There is no known technique for determining assay and simultaneous estimate of Lamivudine, Tenofovir, and Doravirine in combination dose form.…”
Section: Introductionmentioning
confidence: 99%